Urban-rural and sex differentials in tuberculosis mortality in Bangladesh: Results from a population-based survey - Sarker, Malabika; Homayra, Fahmida; Rawal, Lal B.; Kabir, Razin; Aftab, Afzal; Bari, Rahmatul; Dzokoto, Agnes; Shargie, Estifanos Biru; Islam, Shayla; Islam, Akramul; Latif, A. H. M. Mahbub (Wiley Online Library, 2022)
This article was published in the Tropical Medicine and International Health [© 2018 John Wiley & Sons Ltd ] and the definite version is available at: https://doi.org/10.1111/tmi.13171 The Journal's website is at: https://onlinelibrary.wiley.com/doi/10.1111/tmi.13171